Sentiment Analysis On Indonesian Tweets about the 2024 Election - Sembiring, Alfan Ramadhan; Dewa, Chandra Kusuma (Politeknik Ganesha Medan, 2025)
This study investigates public sentiment on Indonesian Twitter regarding the 2024 General Election, employing machine learning and deep learning techniques, including Naïve Bayes, Support Vector Machines (SVM), Long Short-Term Memory (LSTM), and Gated Recurrent Unit (GRU). The dataset was collected using a Tweet Harvest method with the keyword